The psychometric properties of the Washington Early Recognition Center Affectivity and Psychosis (WERCAP) screen in adults in the Kenyan context: Towards combined large scale community screening for affectivity and psychosis. (December 2019) - Ndetei, David; Pike, Kathleen; Mutiso, Victoria; Tele, Albert; Gitonga, Isaiah; Rebello, Tahilia; Musyimi, Christine; Mamah, Daniel
Highlights: This is the first study to study the psychometric properties of Washington Early Recognition Center Affectivity and Psychosis (WERCAP) in Kenya. WERCAP has good psychometric properties in the adult population in Kenya. It can be self-administered or read to the patients by a trained community based lay person. WERCP has the potential for use in mass screening at the same time for affectivity and psychosis in adult patients. Abstract: There is a need for screening for early symptoms of psychosis and affectivity at community level to promote early diagnosis and management. Any screening instrument should have good psychometric properties. One such instrument is the Washington Early Recognition Center Affectivity and Psychosis (WERCAP) Screen that has been used in the USA, Kenya and Rwanda. However, its properties have not been studied outside the USA, and not in adults. The study aims to document the psychometric properties of the WERCAP Screen in Kenyan adults with positive screens on the WHO mental health treatment GAP- Intervention Guidelines (mhGAP-IG). We administered the WERCAP Screen and a gold standard – the Mini-International Neuropsychiatric Interview (MINI-Plus) section on psychosis to 674 Kenyan adults who had screened positive on the WHO mhGAP-IG. Out of these, 464 (68.84%) scored positive for both affectivity and psychosis sections on the MINI-Plus. The WERCAP affectivity and psychosis scales had good psychometric properties as screening measures, with a cut-off point of 22 for affectivity and 20 for psychosis. The WERCAP Screen has the potential for combined scale up screening for affectivity and psychosis in Kenyan population.